Analisis Yuridis Upaya Negara terhadap Perlindungan Hak-Hak Anak di Masa Pandemi Covid-19 Analisa terhadap Undang-Undang Perlindungan Anak No.35 Tahun 2014 - Andoko; Beby Sendy; Irma Fatmawati (Bandung Conference Series: Law Studies, 2022)
Abstract. The new normal era is a necessity and must be faced by all countries until the discovery of the Covid-19 vaccine. The implementation of this new normal era policy has caused public debate regarding various public concerns, especially the state's readiness to guarantee the safety of the population from Covid-19 transmission, especially in protecting children in fulfilling their life needs. right. This paper aims to find out the organizers of child protection in providing protection and fulfillment of children's rights in new normal behavior during the Covid-19 pandemic and to find out the implementation of policies to protect children's rights in new normal behavior during the Covid-19 pandemic. This research uses doctrinal law research. Sources of legal information use primary legal materials (regulations and related documents) for further qualitative analysis. The approach used is a statutory approach and a conceptual approach in helping to solve the problem formulation. This study concludes that the right effort to face the new normal era is to strengthen child protection based on children's rights, starting from parents, families, communities, and the government during the pandemic. Related to the policy determination of the schedule for children to enter school during the new normal era in the midst of the Covid-19 pandemic. The key to child protection in the new normal era is the health protocol rules that can serve as guidelines for parents and child caretakers and the fulfillment of children's main rights in the new normal era is the aspect of child health and safety. Abstrak. Era new normal merupakan keniscayaan dan harus dihadapi oleh semua negara hingga penemuan vaksin penyakit Covid-19. Pemberlakuan kebijakan era new normal ini menimbulkan perdebatan publik terkait berbagai kekhawatiran masyarakat, terutama kesiapan negara menjamin keselamatan penduduk dari penularan Covid-19, khususnya dalam perlindungan anak dalam memenuhi pemenuhan kebutuhan hidupnya. hak. Tulisan ini bertujuan untuk mengetahui penyelenggara perlindungan anak dalam memberikan perlindungan dan pemenuhan hak anak dalam perilaku new normal selama masa pandemi Covid-19 dan untuk mengetahui implementasi kebijakan terhadap perlindungan hak anak dalam perilaku new normal selama masa Covid-19 pandemi. Penelitian ini menggunakan penelitian hukum doktrinal. Sumber informasi hukum menggunakan bahan hukum primer (peraturan dan dokumen terkait) untuk analisis kualitatif lebih lanjut. Pendekatan yang digunakan adalah pendekatan perundang-undangan dan pendekatan konseptual dalam membantu pemecahan rumusan masalah. Penelitian ini menyimpulkan bahwa upaya yang tepat untuk menghadapi era new normal adalah dengan memperkuat perlindungan anak berdasarkan hak-hak anak, mulai dari orang tua, keluarga, masyarakat, dan pemerintah selama masa pandemi. Terkait dengan penetapan kebijakan jadwal anak masuk sekolah saat era new normal di tengah pandemi Covid-19. Kunci perlindungan anak di era new normal adalah aturan protokol kesehatan yang dapat menjadi pedoman bagi orang tua dan pengasuh anak serta pemenuhan hak utama anak di era new normal adalah aspek kesehatan dan keselamatan anak.